Age‐related estimates of aggregate g‐ratio of white matter structures assessed using quantitative magnetic resonance neuroimaging. Issue 8 (17th February 2021) - Bouhrara, Mustapha; Kim, Richard W.; Khattar, Nikkita; Qian, Wenshu; Bergeron, Christopher M.; Melvin, Denise; Zukley, Linda M.; Ferrucci, Luigi; Resnick, Susan M.; Spencer, Richard G.
Abstract: The g ‐ratio, defined as the inner‐to‐outer diameter of a myelinated axon, is associated with the speed of nerve impulse conduction, and represents an index of axonal myelination and integrity. It has been shown to be a sensitive and specific biomarker of neurodevelopment and neurodegeneration. However, there have been very few magnetic resonance imaging studies of the g ‐ratio in the context of normative aging; characterizing regional and time‐dependent cerebral changes in g ‐ratio in cognitively normal subjects will be a crucial step in differentiating normal from abnormal microstructural alterations. In the current study, we investigated age‐related differences in aggregate g ‐ratio, that is, g ‐ratio averaged over all fibers within regions of interest, in several white matter regions in a cohort of 52 cognitively unimpaired participants ranging in age from 21 to 84 years. We found a quadratic, U‐shaped, relationship between aggregate g ‐ratio and age in most cerebral regions investigated, suggesting myelin maturation until middle age followed by a decrease at older ages. As expected, we observed that these age‐related differences vary across different brain regions, with the frontal lobes and parietal lobes exhibiting slightly earlier ages of minimum aggregate g ‐ratio as compared to more posterior structures such as the occipital lobes and temporal lobes; this agrees with the retrogenesis paradigm. Our results provide evidence for a nonlinear association between age and aggregate g ‐ratio in a sample of adults from a highly controlled population. Finally, sex differences in aggregate g ‐ratio were observed in several cerebral regions, with women exhibiting overall lower values as compared to men; this likely reflects the greater myelin content in women's brain, in agreement with recent investigations. Abstract : Using quantitative MRI, we investigated age‐related differences in aggregate g ‐ratio in several white matter regions in a cohort of 52 cognitively unimpaired participants ranging in age from 21 to 84 years. We found a quadratic, U‐shaped, relationship between aggregate g ‐ratio and age in most cerebral regions investigated. Sex differences were also observed in several cerebral regions.